Qualitative research in Human Sciences. Criteria for preparing scientific articles - Loayza Maturrano, Edward Faustino (2020)
Qualitative research enjoys a renewed attention product of an interdisciplinary orientation of Human Sciences and Education. The main purpose of this work is to establish the general criteria that all qualitative research should develop and that all scientific articles should explain. The methodology used in this study is of a qualitative nature whose design is framed in the discourse analysis. The main results of the research explain the existence of general criteria in qualitative research expressed in scientific articles in the field of Human Sciences and Education. The conclusions of the study indicate that the scientific articles of qualitative research meet the general criteria proposed; However, some of these criteria are not explicit, which indicates that qualitative scientific articles have a flexible organizational structure.